Peran Manajemen Berbasis Sekolah Dalam Meningkatkan Mutu Pendidikan Studi Literatur Komprehensif - Alina, Hamsin; Arbain, Rukmin; Tualeka, Erwin (Peneliti.net, 2025)
School-Based Management (SBM) is a decentralized approach to education management that gives schools greater authority to manage resources and make decisions to improve the quality of education. This study aims to comprehensively analyze the role of SBM in improving the quality of education through research that includes concepts, implementation, and the resulting impacts. This study uses a literature study method by reviewing various sources of literature, including academic journals, books, and relevant research reports. The results of the study indicate that the implementation of SBM has a positive impact on improving the quality of education through various mechanisms, such as increasing stakeholder participation, efficient resource management, and increasing accountability and transparency in decision making. The main factors that support the effectiveness of SBM include strong principal leadership, active involvement of teachers and parents, and consistent government policy support. However, several challenges were also found in the implementation of SBM, such as limited managerial capacity of principals, resource disparities between schools, and resistance to change in the educational environment. The implications of this study confirm that SBM can be an effective strategy in improving the quality of education if implemented with a systematic approach and based on the context of each school. Therefore, the policy recommendations provided include increasing the managerial capacity of school principals, optimizing the role of school committees, and strengthening the monitoring and evaluation system to ensure the effectiveness of MBS implementation. Thus, MBS can contribute significantly to improving the quality of sustainable and equitable education.